Subjective Precarity and the Normalization of Work–Life Imbalance: Chinese Female Journalists’ Lived Experiences - Li, Lingyu (AoIR Selected Papers of Internet Research, 2026)
Prior research showed that long hours, nontraditional schedules, and the integration of digital technologies shape journalists’ ability to balance professional and personal lives (Snyder et al., 2021). This study examines how Chinese female journalists experience and normalize work–life imbalance over time, even while recognizing its negative impacts.This study focuses on Chinese female journalists in their early and mid-career stages, before becoming mothers— a group often overlooked in existing literature, which typically emphasizes married women with children.Using precarity as a conceptual framework, this study draws on three focus group interviews, each with 5-6 journalists from local and regional print media. Thematic analysis is employed to examine how they perceive their work-life blending experiences.The findings reveal three central tensions:- While journalists accept work-life blending as a given, they simultaneously acknowledge that its negative consequences outweigh its benefits, especially in terms of their well-being and health.- Despite believing that work-life imbalance is inevitable, they continue to seek temporary detachment from work, often using technology or relying on family members to help them disengage.- The blending of work and life is emotionally charged but experienced differently across career stages.This study contributes to the understanding of journalistic precarity by exploring its emotional dimensions, highlighting how work-life imbalance fosters feelings of entrapment, exhaustion, and instability.